Thermal degradation of lead halide perovskite surfaces. Issue 97 (18th November 2022) - Kammlander, Birgit; Svanström, Sebastian; Kühn, Danilo; Johansson, Fredrik O. L.; Sinha, Swarnshikha; Rensmo, Håkan; Fernández, Alberto García; Cappel, Ute B.
Abstract : The thermal degradation temperature of perovskite single crystal surfaces (MAPbI3, MAPbBr3, FAPbBr3 ) depends more on the halide than on the organic cation. However, different solid degradation products form depending on the cation. Abstract : Commercial use of lead halide perovskites requires improved thermal stability and therefore a better understanding of their degradation mechanisms. The thermal degradation of three clean perovskite single crystal surfaces (MAPbI3, MAPbBr3, FAPbBr3 ) was investigated using synchrotron-based photoelectron spectroscopy. Central findings are that the halide has a large impact on thermal stability and that the degradation of formamidnium results in the formation of a new organic species at the FAPbBr3 crystal surface.